1998
DOI: 10.1037/0012-1649.34.3.555
|View full text |Cite
|
Sign up to set email alerts
|

Arousal modulation in cocaine-exposed infants.

Abstract: The ability to modulate arousal is a critical skill with wide-ranging implications for development. In this study, the authors examined arousal regulation as a function of levels of prenatal cocaine exposure in 107 infants at 4 months of age using a "still-face" procedure. Facial expressions were coded. A greater percentage of heavily cocaine-exposed infants, compared with those who were unexposed to cocaine, showed less enjoyment during en face play with their mothers and continued to show negative expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
99
2
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(106 citation statements)
references
References 75 publications
(110 reference statements)
4
99
2
1
Order By: Relevance
“…These findings are not limited to autonomic measures of reactivity. In fact, previous studies measuring the hypothalamic pituitary axis (HPA) have found group differences in baseline cortisol at this age among substance-exposed infants (Bendersky & Lewis, 1998b;Jacobson, Bihun, & Chiodo, 1999;Ramsey, Bendersky, & Lewis, 1996;Veira, Eiden, & Schuetze, 2004) which has been interpreted as increased stress reactivity (Bendersky & Lewis, 1998b;Gunnar & White, 2001). Thus, our findings lend additional support to the idea that cocaine-exposed infants have increased levels of stress reactivity, relative to nonexposed infants.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are not limited to autonomic measures of reactivity. In fact, previous studies measuring the hypothalamic pituitary axis (HPA) have found group differences in baseline cortisol at this age among substance-exposed infants (Bendersky & Lewis, 1998b;Jacobson, Bihun, & Chiodo, 1999;Ramsey, Bendersky, & Lewis, 1996;Veira, Eiden, & Schuetze, 2004) which has been interpreted as increased stress reactivity (Bendersky & Lewis, 1998b;Gunnar & White, 2001). Thus, our findings lend additional support to the idea that cocaine-exposed infants have increased levels of stress reactivity, relative to nonexposed infants.…”
Section: Discussionmentioning
confidence: 99%
“…According to this model, the adaptation to challenging situations depends on an individual's threshold for activation of the catecholamine and norepinephrin arousal system, and this threshold may be impaired by the prenatal toxicant exposure. The ability to modulate arousal is a critical skill, with wideranging implications for development [10]. Animal models have also shown that prenatal and early postnatal exposure to nicotine can modulate catecholamine gene expression or neuroendocrine regulation [33,81], and recent evidence from animal and human studies has shown that maternal stress may mediate associations between socioeconomic adversity and early childhood cognition [52,63,64].…”
Section: Discussionmentioning
confidence: 99%
“…However, if examinations of at-risk populations are included, the number of extant studies becomes relatively larger. For example, children who have been exposed prenatally to cocaine demonstrate deficits in basic emotion expression such as delayed or idiosyncratic expression (e.g., Alessandri & Lewis, 1996a;Alessandri, Sullivan, Imaizumi, & Lewis, 1993;Bendersky, Alessandri, & Lewis, 1996). Other research has suggested that infants of mothers with high levels of depressive symptoms exhibit a lot of negative emotions and fewer positive emotions during learning tasks (e.g., Lundy, Field, & Pickens, 1996;Pickens & Field, 1993).…”
Section: Emotion Expression: Psychopathological Populationsmentioning
confidence: 99%